Ansamble Perkusi (Komposisi Musik SMK Negeri 3 Padang) - Dodo Pratama Ardedi; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2019)
This work aims to display the creativity of female students in school, and it can be a reference for teachers in developing talents, interests and creativities of female students. The form of this artwork is percussion ensemble, the author will combine the rhythmic patterns of single stroke, double stokes, and triols in 4/4 hours with a simple form. It does not only focus on the instrument itself, the author will also combine with vowels to build atmosphere. Percussion ensemble is a musical composition that is adopted from the game of similar percussion instrument, such execution is very interesting because there is no melody instrument here. the incorporation of the rhythmic pattern of single stroke percussion instrument, dooble stokes, and triols can show a rhythm by exploring it into the percussion instruments used. Percussion ensemble is played by six players that consist of two tambua players, one snare drum player, one floor drum player, one cymbal and cowbell player, one bongo player and one of triangel player.